Sowing and Harvesting Measures to Cope with Challenges of Cover Crops Experienced by Finnish Farmers - Peltonen-Sainio, Pirjo; Jauhiainen, Lauri; Joona, Juuso; Mattila, Tuomas; Hydén, Tony; Känkänen, Hannu (MDPI AG, 2023)
Farmers may promote the cultivation of under-sown cover crops (CCs) in various ways without jeopardizing the yield of a cash crop. With this survey, we aimed to understand how Finnish farmers manage possible challenges with under-sown CCs. A farmer survey was carried out in 2021. We invited 6493 farmers who had selected CCs as a registered measure to answer a questionnaire with 20 statements (a Likert scale), and 1130 responded (17.4%). A Cochran–Mantel–Haenszel test was used to measure the strength of the association between 11 farm/farmer characteristics of the respondents and 20 statements. Responses indicated that farmers often took under-sown CCs into account during the growing season. Sowing was considered an especially critical measure and the CC seeding rate was often assessed with a test run before sowing. Thirty-nine per cent of the respondents had made investments, most often to facilitate sowing. The farmers usually adjusted the fertilizer rate only according to the cash crop. Early harvesting of a cash crop was considered important by 58% of farmers to ensure that the CCs do not hamper the harvest. Farmers harvested cash crops as soon as they matured and were harvestable, though they had mixed views on whether CCs impacted the quality of the cash crop. Subsidized, investing farmers were likely to be oriented towards the benefits from the ecosystem services provided by CCs. Their experiences should be shared among the farming community to support the large-scale implementation of CCs.
Keywords: maanpeitekasvit; viljely; kylvö; korjuu; kyselytutkimus; maanviljelijät; konehankinnat; cover crops; crop management; harvesting; investment; sowing; survey